(untitled) (Fiep Bulletin - online, 2013)
The temporomandibular articulation problems, especially the incidence of orofacial pain has growing up gradually due to stress and the day’s tensions that are experienced by the people day by day. Because of these problems, there is a necessity of physiotherapy’s treatment that is managed to that dysfunction. This search compared the pain’s physiotherapy treatment resulting of the temporomandibular dysfunction using handmade techniques and electrotherapy and phototherapy in female patients at the ages of 20 to 40 years old. The conclusion of this investigation, according to the data’s analysis, was the techniques choose showed up useful to alleviate symptoms referred by the subjects of the search.